INTERFERENCE OF ASCORBIC ACID AND WATER CONTENT ON AUTOXIDATION OF SUNFLOWER SEED OIL IN MODEL FOOD SYSTEM - Salih Hommady Sultan (Mesopotamia Journal of Agriculture)
In this study different concentration of ascorbic acid was used as antioxidant(0.1, 0.2, 0.3 and 0.4%) from the oil weight percentage in food model system. Water content 5,10,20,30% from the dry base. Sample were kept in transparent plastic bags exposed to normal light in room temperature from march till June. The bags were completely sealed in order to restrict oxygen absorbing .Pv value was used as a criteria for autoxidation progress at storage period . Results showed that the oxidation was suppressed in the system low moisture (5%) at beginning weeks. The process was enhanced in system with high water content and ascorbic acid concentration (0.2, 0.3, and 0.4%).After one month of storage all samples unaffected in all percentage used.